The Effectiveness of Using Educandy Media towards Students’ Vocabulary - Salsabila, Putri Bahjah; Syafrizal; Handayani, Ika (English Education Department, 2024)
This research aims to evaluate the effectiveness of using Educandy media towards students’ vocabulary of eighth-grade students at SMPN 10 Serang. A quantitative approach with a quasi-experimental design was utilized to systematically analyze the impact of Educandy on students' vocabulary acquisition. Participants were divided into two classes, selected through purposive sampling. The main data collection tool was a test, consisting of a pre-test and a post-test. The pre-test, administered at the study's outset, established a baseline of students' vocabulary knowledge, while the post-test, given at the study's conclusion, assessed any vocabulary improvements due to the Educandy intervention. Data were analyzed using a T-test to compare the performance of the two classes. Results indicated significant differences in vocabulary acquisition between the experimental group, which used Educandy, and the control group, which did not. The significance value (2-tailed) was below 0.05, indicating a statistically significant improvement in the vocabulary of students who used Educandy media. Consequently, the alternative hypothesis (Ha) was accepted, and the null hypothesis (H0) was rejected. These findings suggest that Educandy media is an effective tool for enhancing vocabulary among eighth-grade students. Thus, it can be concluded that Educandy media effectively improves the vocabulary of eighth-grade students at SMPN 10 Serang.